2012
DOI: 10.1123/rsj.36.2.78
|View full text |Cite
|
Sign up to set email alerts
|

An Examination of Variables Related to Student Employment in Campus Recreation Programs

Abstract: Previous literature on student employment within campus recreation departments has focused on a variety of work-related factors, but has been limited by examining single institutions. The current study extended this area of research by examining 290 recreation student employees at 11 institutions located throughout the United States to determine how important five work-related variables were to student employment. Results indicated all variables were rated high in importance, but ability to work around class s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 20 publications
(50 reference statements)
0
8
0
Order By: Relevance
“…Turner, Jordan, and DuBord (2005), studied the importance of organizational commitment in keeping students employed in campus recreation. Johnson, Kaiser and Bell (2012) researched variables in regards to students being employed in campus recreation. Forrester (2014) articulated that for years the field of campus recreation has championed the benefits of participation in collegiate recreation sport activities, facilities, programs and services.…”
mentioning
confidence: 99%
“…Turner, Jordan, and DuBord (2005), studied the importance of organizational commitment in keeping students employed in campus recreation. Johnson, Kaiser and Bell (2012) researched variables in regards to students being employed in campus recreation. Forrester (2014) articulated that for years the field of campus recreation has championed the benefits of participation in collegiate recreation sport activities, facilities, programs and services.…”
mentioning
confidence: 99%
“…However, working on campus results in only minor differences within these levels from nonworking students. One study of on-campus recreational employees found that social interactions acted as one of the significant positive factors for students' employment decisions (Johnson, Kaiser, & Bell, 2012).…”
Section: Academic Performancementioning
confidence: 99%
“…No relationship existed for credit hour enrollment. Other research on campus recreation employees has focused on job satisfaction (Johnson et al, 2012), socialization (Griffith, Walker, & Collins, 2011), organizational culture (Wells & Lower, 2016), and position-specific outcomes (Griffith et al, 2011;Miller & Grayson, 2006).…”
Section: Campus Recreationmentioning
confidence: 99%
“…There is a growing body of research assisting practitioners in understanding the connection between student employment and college student development (Astin, 1984;Salisbury, Pascarella, Padgett, & Blaich, 2012). In addition, there is research focused directly on college students working in collegiate recreation environments (Hall, 2013;Johnson, Kaiser, & Bell, 2012;Kellison & James;2011;Miller & Grayson, 2006;Wallace Carr, 2005) as well as literature on student employment and leadership development (Luzzo, 1999;Perozzi, 2009).…”
Section: Cara W Mcfadden Julia Wallace Carrmentioning
confidence: 99%